User behavior in ubiquitous online environmentsaUser behavior in ubiquitous online environments - Pelet, Jean-Eric, 1976- editor; Papadopoulou, Panagiota, 1975- editor (Hershey, PA : Information Science Reference, an imprint of IGI Global, 2014)
"This book explores how users interact with mobile devices and applications in an array of contexts, providing relevant theoretical frameworks and the latest empirical research on ubiquitous computing"--provided by publisher